Perancangan Sistem Informasi Pembelajaran (E-Learning) Sekolah Menengah Atas Berbasis Web - Ispandi Ispandi (JURIKOM (Jurnal Riset Komputer), 2018)
This e-Learning or computerized learning method provides convenience in the teaching and learning process because it uses internet media, intranet, or other computer networks so that it allows the delivery of subject matter to students. The learning information system that the writer makes covers the provision of learning material that can be read and studied anytime and anywhere, then provides practice questions to train the ability to master the material that has been learned that can be accessed directly whenever and wherever, and provide results direct assessment after the user exercises the questions so that the user is able to measure the extent to which the mastery of the material has been mastered.